Wechselstrom : Sammlung Hauser und Wirth / Teil 2. - Groys, Boris; Heynen, Julian; Unterdörfer, Michaela; Sammlung Hauser und Wirth, St.Gallen (Köln : Oktagon Verlag Köln, 2001)
Roth, Dieter ; Signer, Roman ; Oursler, Tony ; Riverhead (New York) ; Giacometti, Alberto ; McCracken, John ; Akkerman, Philip ; Ahtila, Eija-Liisa ; Mangold, Robert ; Gonzalez-Torres, Felix ; Nauman, Bruce ; Peyton, Elizabeth ; Bulloch, Angela ; Fischli & Weiss ; Douglas, Stan ; Graham, Rodney ; Clark, Larry ; Kippenberger, Martin ; Williams, Christopher ; Pettibon, Raymond ; Rondinone, Ugo ; Eichhorn, Maria ; West, Franz ; Rist, Pipilotti ; Rhoades, Jason ; Schnyder, Jean-Frederic ; Graham, Dan ; Thater, Diana ; Goldstein, Zvi
biog., bibliog. p. 96-99
Duits & Engels
Wechselstrom, Sammlung Hauser und Wirth in der Lokremise, St. Gallen, 13.05. - 14.10.2001
boek